Visual Storytelling and Narrative Marketing in a UNESCO Global Geopark: A Strategic Branding Intervention For Hanjeli Tourism Village - Ganjar Mohamad Disastra; Donni Junipriansa; Rangga Ardiansyah (International Journal Of Community Service, 2026)
The global tourism landscape is witnessing a significant paradigm shift toward authentic, meaningful, and sustainable experiences. In response, Community-Based Tourism (CBT) has emerged as a vital strategic framework. Hanjeli Tourism Village, situated within the Ciletuh-Palabuhanratu UNESCO Global Geopark, offers a distinctive Unique Value Proposition (UVP) through the cultivation of Coix lacryma-jobi L. (Hanjeli)—a nutrient-dense functional food deeply embedded in local cultural heritage. Despite this potential, the destination faces critical branding and digital promotion deficits, resulting in a strategic misalignment between its intrinsic brand identity and its perceived image among prospective travelers. This study examines a strategic marketing intervention leveraging narrative marketing and visual storytelling via promotional videos. By transforming Hanjeli’s core tangible and intangible assets into a cohesive brand narrative, this approach aims to enhance brand awareness and stimulate visit intentions. Beyond marketing objectives, the intervention is designed to catalyze positive socio-economic and socio-cultural outcomes for the local community, fostering long-term resilience and sustainability.